Pola Komunikasi Narapidana Lapas Kelas I Bandar Lampung - Muhammad Refaldi; Maman Suherman (UNISBA Press, 2022)
Abstract. Communication is an important role for humans because humans are social creatures where social beings need each other and their social environment as a means to socialize. To find out the communication patterns and obstacles that occur in Class 1 prisons, Bandar Lampung prisoners are running properly. In this study using a qualitative case study method with data collection observations, interviews. Humans also act as social beings who are interconnected and related to the environment and where they live. In achieving success, a good communication strategy is needed, especially in achieving success, a good strategy is needed, especially in disciplining Class I prison inmates in Bandar Lampung. A leader or commander of a correctional institution must have good skills in developing communication strategies and how to communicate it to prisoners in order to discipline inmates and officers. Abstrak. Komunikasi merupakan suatu peranan penting bagi manusia karena manusia merupakan makhluk sosial dimana mahluk sosial saling membutuhkan satu sama lain dan lingkungan sosialnya sebagai sarana untuk bersosialisasi. Untuk mengetahui pola komunikasi dan hambatan yang terjadi di lapas kelas 1 narapidana Bandar Lampung berjalan dengan semestinya. Dalam penelitian ini menggunakan metode study kasus kualitatif dengan pengambilan data observasi,wawancara. Manusia pun berlaku sebagai makhluk sosial yang saling berhubungan dan keterkaitannya dengan lingkungan dan tempat tinggalnya. Dalam mencapai keberhasilan diperlukan strategi komunikasi yang baik terutama dalam mencapai keberhasilan diperlukan strategi yang baik terutama dalam mendisiplinkan narapidana Lapas Kelas I Bandar Lampung. Seorang pempinan atau komandan lembaga pemasyarakatan harus memiliki kemampuan yang baik dalam menyusun strategi komunikasi dan cara mengkomunikasikannya kepada narapidana guna mendisiplinkan para narapidan maupun petugas.